Прооксидантно-антиоксидантний баланс у печінці щурів після холодової ішемії в присутності 2,4-динітрофенолу та наступної реперфузії - Черкашина, Д.В.; Ткачова, О.М.; Сомов, О.Ю.; Лебединський, О.С.; Семенченко, О.А.; Грищенко, В.І.; Петренко, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
The influence of the presence of an oxidative phosphorylation uncoupler 2,4-dinitrophenol (DNP) in a storage solution on the pro-oxidant/antioxidant balance in rat liver after 18-h cold ischemia and the following normothermic reperfusion is investigated. The presence of DNP on the cold ischemia stage led to the partial mitochondrial uncoupling, which was confirmed by suppression of lipid peroxidation intensity with prevention of antioxidant enzyme activity decrease (catalase, GSH-peroxidase, GSH-reductase). After the DNP removal during the following normothermic reperfusion, the gradual recovery of oxidative phosphorylation coupling occurs. This fact results in the improvement of the pro-oxidant/antioxidant liver state: a low level of TBA-active products and a high activity of catalase, GSH-peroxidase, and G6PDH are preserved. Thus, the supplementation of a storage solution with DNP seems to be the perspective approach to the prevention of isolated liver ischemia-reperfusion injury.